The role of school connectedness in the prevention of youth depression and anxiety: a systematic review with youth consultation - Monika Raniti; Divyangana Rakesh; George C. Patton; Susan M. Sawyer (BMC, 2022)
Abstract Background School connectedness reflects the quality of students' engagement with peers, teachers, and learning in the school environment. It has attracted attention from both the health and education sectors as a potentially modifiable protective factor for common mental health problems. However, the extent to which school connectedness may prevent the onset of youth depression or anxiety or promote their remission is unclear. This systematic review examined evidence for prospective relationships between school connectedness and depression and anxiety, and the effect of interventions to improve school connectedness on depression and anxiety. Methods We searched MEDLINE, PsycINFO, PubMed, and ERIC electronic databases for peer-reviewed quantitative longitudinal, or intervention studies published from 2011-21 in English examining relationships between school connectedness and anxiety and/or depression. Participants were 14-24 years old when depression and anxiety outcomes were assessed in any education setting in any country. We partnered with five youth advisers (aged 16-21 years) with lived experience of mental health problems and/or the schooling system in Australia, Indonesia, and the Philippines to ensure that youth perspectives informed the review. Results Our search identified 3552 unique records from which 34 longitudinal and 2 intervention studies were ultimately included. Studies were primarily from the United States of America (69.4%). Depression and anxiety outcomes were first measured at 14 years old, on average. Most studies found a significant protective relationship between higher levels of school connectedness and depressive and/or anxiety symptoms; more measured depression than anxiety. A few studies found a non-significant relationship. Both intervention studies designed to increase school connectedness improved depression, one through improvements in self-esteem and one through improvements in relationships at school. Conclusions These findings suggest that school connectedness may be a novel target for the prevention of depression and anxiety. We were not able to determine whether improving school connectedness promotes remission in young people already experiencing depression and anxiety. More studies examining anxiety, diagnostic outcomes, and beyond North America are warranted, as well as intervention trials. Trial registration PROSPERO 2021 CRD42021270967.